Psychometric validation of the Brain Symptom and Impact Questionnaire (BASIQ) version 1.0 to assess quality of life in patients with brain metastases. (January 2015) - Thavarajah, Nemica; Ray, Saurabh; Bedard, Gillian; Zhang, Liying; Cella, David; Wong, Erin; Danjoux, Cyril; Tsao, May; Barnes, Elizabeth; Sahgal, Arjun; Soliman, Hany; Pulenzas, Natalie; et al.
SUMMARY : Objective: To test the reliability, clinical and psychometric validity of the Brain Symptom and Impact Questionnaire (BASIQ) in patients with brain metastases.Methods: Brain metastases patients were interviewed using the BASIQ, Functional Assessment of Cancer-Brain (FACT-Br) and FACT-General (FACT-G) at baseline, with a follow-up assessment at 1 month.Results: Forty patients had complete one data and the median age was 64 years. Patients with higher KPS, ECOG of 2, primary breast cancer, or >3 brain metastases, scored higher on the symptom scale of the BASIQ. All subscales showed no significant change in patient symptoms from baseline to follow-up.Conclusion: This study supports that the reliability, clinical and psychometric validity of BASIQ to be used in brain metastases patients.